Pengaruh pembayaran sistem online terhadap penerimaan pajak bumi dan bangunan - Ardana Putri, Allya Nadia Itra (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This research aims to determine how online payment systems impact tax revenue from land and buildings (Case Study on the Regional Tax Revenue Agency for Central Bandung City UPT). This study employs a descriptive-quantitative approach. Questionnaires and book searches were used to collect data from the UPT Tengah Regional Revenue Management Agency in Bandung City. The information in this research was derived from 50 questionnaires completed by taxpayers who paid using the UPT Tengah Bandung City online system. The data is presented on an ordinal measure. With the aid of SPSS software, the data analysis method used in this study included fundamental linear regression analysis using the standard assumption test in the form of a normality test, a heteroscedasticity test, a linearity test, a T-test, and a coefficient of determination test. The findings revealed that the online system payment variable (X) influenced land and building tax revenues (Y).